(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Pegmatites are an extremely, coarse-grained igneous rocks of granitic composition, constituting of mainly large crystals of quartz, feldspar and mica. Their occurrence cut across various formations, but mostly around granitoids. They are known to host industrial, rare metals, exotic minerals and gemstones of economic value. Due to the continuous demands and recently discovered uses of some of these minerals, its continuous exploration can never be over-emphasized. Pegmatites occurrence in Nigeria were formerly confined to certain quadrants but resent research has proved they also exist in other zones too. Its occurrence in Ogodo-Odobola area is a recent discovery with scantily available literature. The Few available research work conducted on pegmatite of the Ogodo-Odobola area in Kogi State, North central Nigeria has been reviewed. The works focused on its feldspar content for economic value and the latter attempted the mineralization potential of the pegmatites. The area is revealed to be underlain by schistose and granitic lithologies and intruded by the pegmatite dykes of various dimensions. However, recent studies on granitic pegmatites have evolved just as the pegmatites, not only concentrating on their industrial potentials but also on rare metal mineralization potentials which presently are a key to unlocking the future technologically. A few of those relevant and recent studies in the field were also reviewed to bring forth new ways of dealing with this present world cake to geoscientists. White micas are a useful mineral for determining the degree of evolution in pegmatites.